Efficacy of washing and disinfection in cattle markets in Ireland. Issue 1 (December 2017) - Connor, Jarlath; Clegg, Tracy; More, Simon
Abstract Background Few studies have reported on the effectiveness of the washing and disinfection methods used in cattle markets in Ireland. Purchasing cattle into recipient herds poses a high biosecurity risk due to the possibility of introducing disease. In Ireland, livestock markets are an important intermediary in the movement of cattle to new herds. Thus disease control strategies need to consider the disease risk associated with moving livestock through markets. Some cattle are also moved directly from markets for slaughter at abattoirs. Washing and disinfection at markets is utilised to reduce faecal contamination in markets, thereby reducing the risk of disease spread among animals and carcass contamination at slaughter. The primary objective of this study was to assess the efficacy of standard washing and disinfection techniques at markets in Ireland in reducing bacterial contamination on internal structures. Total viable counts (TVC) of colony forming units (CFU) were used as indicators of bacterial contamination, which could include pathogens of public and animal health concern. Four hundred and seventy nine samples were taken mainly from pen floors and the TVC enumerated for each sample. Results Washing and disinfection was effective at significantly reducing TVCs on floors and metal bars of market holding pens, but residual contamination remained. Washing market pens only (no disinfection), followed by a rest period between batches of cattle (6.5 days) was as effective at reducing TVCs as washing followed by disinfection and a shorter rest period (5.5 days). Conclusions Markets are a potential reservoir for microbial contamination with a resultant increased risk of disease spread by cattle moving through markets into new herds, and carcass contamination for cattle moving directly to slaughter. Therefore, market managers need clear advice and guidance on the development of hygiene programmes that are suitable for use in livestock markets.